AMH as the primary marker for fertility. Issue 6 (December 2019) - Dewailly, Didier; Laven, Joop
Abstract : In women, the anti-Müllerian hormone (AMH) is secreted by the granulosa cells of growing follicles. Its measurement is strongly correlated with antral follicle count and represents a reliable marker of ovarian reserve. It also has the advantage of being highly reproducible since it has little variation within and between cycles. However, although it seems to be a good quantitative reflection of the ovarian reserve, it does not assess oocyte or embryo quality. This drawback precludes any good prediction of female fertility in the general population as well as in specific subgroups of patients. However, the AMH assay can become an indirect marker of the remaining female fertile years in some cases such as in those women who are at risk for premature ovarian failure or in those suffering from polycystic ovary syndrome. Its interest is no more to be proven in assisted reproductive technology where it is a valuable aid to the choice of the proposed techniques, ovarian stimulation protocols and gonadotropin dosage. AMH is finally very informative in monitoring cancer patients having received gonadotoxic drugs or having undergone mutilating ovarian surgeries. In conclusion, although it cannot be considered as a reliable predictor of pregnancy in women, AMH is now a useful tool in the management and treatment of female infertility.